IMPLEMENTASI KODE ETIK PEMBINA BIAK KOMISI ANAK KEUSKUPAN SURABAYA - Nugraha, Aditya Bima; Supriyadi, Agustinus (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2024)
The purpose of this study is to describe and analyze the definition of Bina Iman Anak Katolik Supervisor, the code of ethics established by the Children's Commission of the Diocese of Surabaya, and its implementation in the Parish of St. Francis of Assisi, Mojorejo. Qualitative research methods were employed, with seven Bina Iman Anak Katolik coaches as informants. The findings reveal that Bina Iman Anak Katolik coaches grasp the code of ethics outlined by the Surabaya Diocese Children's Commission and perceive it as a standard for their training. The code has been effectively implemented, focusing on eight key points: accompanying children during activities, aiding them in liturgical matters, supporting them technically with families and colleagues, integrating them with the community, addressing potential issues, guiding them under leadership, and attending to individual needs.